Crigler-Najjar Syndrome - current state of knowledge, overview of etiology, symptoms, diagnosis and treatment methods - Wawrzkowicz, Jakub; Korga, Monika; Pawlik, Paweł; Zaroda, Przemysław; Dąda, Paweł; Niewinna, Patrycja; Żuchowski, Michał; Mańdziuk, Dominika; Kołodziej, Klaudia; Kołodziej, Wojciech (Quality in Sport, 2024)
Crigler-Najjar syndrome is an autosomal recessive genetic disorder characterized by a mutation in the UGT1A1 gene, resulting in a complete deficiency of uridine diphosphate glucuronosyltransferase enzyme in hepatocytes. This leads to jaundice due to elevated levels of indirect bilirubin in the blood. Two types of the syndrome are distinguished: type I and type II. Untreated disease can lead to serious complications, often necessitating liver transplantation. Therefore, there is a constant need for new treatment methods. This article provides an overview of the clinical symptoms, pathophysiological mechanisms, and current diagnostic and treatment methods for this condition. Although Crigler-Najjar syndrome is rare, its diagnosis and treatment pose clinical challenges due to potential complications associated with bilirubin accumulation. The article also discusses therapeutic perspectives, such as phototherapy and plasma exchange, and provides recommendations for patient care. Given the limited availability of information on Crigler-Najjar syndrome, this review aims to increase clinical awareness and improve the quality of care for patients with this rare disorder.